KENDALA DALAM PELAKSANAAN PENEGAKAN HUKUM TERHADAP PRAKTIK PARANORMAL SEBAGAI TINDAK PIDANA - Yusi Permatasi; Yuwono Prianto (Jurnal Hukum Adigama, 2018)
In Society, Paranormal practices is considered as common things. Paranormal Practices is used for any good and also for crime, so to cope with the activities, government had regulated the act to control the crime by using paranormal background. The paranormal practices have been included as criminal acts. It has regulated in article 545 and article 546 of the criminal law act and set on as supernatural powers activity. As time passes, there are constraint in the alleviation law it’s law enforcement. This research was done with empirical or law sociological point of view, where Lawrence M. Friedman state that the elements of the legal system consist of Legal Structure, Legal Substance, and Legal Culture. The result of this research is the paranormal practices are differentiate by it used which is good or bad. The bad paranormal practices cause loss for society. This gave rise to uncertainty of law enforcement on the paranormal practices, therefore it need a deep research which is not only from the law enforcement point of view, but also the religious and cultural represented by figure.